The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/agronomy10040492
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiology of Hemp Retting in a Controlled Environment: Steering the Hemp Microbiome towards More Consistent Fiber Production

Abstract: Industrial hemp (Cannabis sativa L.) production is increasing dramatically in the US due to recent changes which lift restrictions on the growth and sale of hemp products; however, due to the decades-long prohibition of hemp, there is a lack of current research with respect to varieties and best agricultural practices for the many uses of this versatile crop. Natural fiber production relies on retting, a microbially-mediated process necessary for the separation of fibers from the plant which can occur unevenly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, the results obtained concerning the Fungi kingdom must be taken with care because precisions concerning the bioinformatics analysis are not available (e.g., sub-sampling size/rarefaction) and certain inaccuracies on the taxonomic affiliation occured (e.g., confusion between the different taxonomic levels; Opisthokonta has been classified as a subkingdom and a phylum). To date, only one study has been conducted on hemp retting by metabarcoding (Law et al, 2020). This study indicated an average OTU richness mean of one hundred.…”
Section: Metabarcoding and The Breakthrough In Knowledge On Retting Mmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the results obtained concerning the Fungi kingdom must be taken with care because precisions concerning the bioinformatics analysis are not available (e.g., sub-sampling size/rarefaction) and certain inaccuracies on the taxonomic affiliation occured (e.g., confusion between the different taxonomic levels; Opisthokonta has been classified as a subkingdom and a phylum). To date, only one study has been conducted on hemp retting by metabarcoding (Law et al, 2020). This study indicated an average OTU richness mean of one hundred.…”
Section: Metabarcoding and The Breakthrough In Knowledge On Retting Mmentioning
confidence: 92%
“…In comparison, the study by Ribeiro et al (2015) identified 66 different bacterial phylotypes. Despite the fact that these two studies involved different environmental conditions - Law et al (2020) conducted hemp retting in a greenhouse under controlled conditions, while Ribeiro et al (2015) collected samples in the field -the OTU or phylotype distributions were similar for the Proteobacteria (85 vs. 77%), Bacteroidetes (8 vs. 11%) and Firmicute (1% or less) but differed for Actinobacteria (2.3 vs. 11%).…”
Section: Metabarcoding and The Breakthrough In Knowledge On Retting Mmentioning
confidence: 99%
“…(Backer et al, 2018), but the involvement of this hypothetical mechanism remains to be validated in this context. Finally, regarding the retting process, several studies have established that pectinolytic Pseudomonas strains are particularly important as natural retting agents for harvested hemp stalks under aerobic conditions (Ribeiro et al, 2015;Liu et al, 2017;Law et al, 2020). Dedicated Pseudomonas spp.…”
Section: Fiber Hemp Cropsmentioning
confidence: 99%
“…In cannabis, bottom-up studies seem undeniably promising given the recent results obtained with existing PGPR strains (Citterio et al, 2005;Jin et al, 2014;Pagnani et al, 2018;Comeau et al, 2021), biocontrol agents (Balthazar et al, 2020(Balthazar et al, , 2021, or commercialized bioproducts (Gonsior et al, 2004;Conant et al, 2017;Kakabouki et al, 2021a,b;Punja, 2021;Punja and Ni, 2021;Scott and Punja, 2021), thus paving the way for future work with existing Pseudomonasbased bioproducts that are already registered for cereals, fruit trees, and greenhouse vegetables (Fischer et al, 2013;Khan et al, 2016). On the other hand, several top-down studies have also started to examine the potential of harnessing cannabis microbiome residents to improve pathogen control (Gautam et al, 2013;Kusari et al, 2013;Qadri et al, 2013;Scott et al, 2018;, salinity tolerance (Afzal et al, 2015), soil phytoremediation (Liste and Prutz, 2006;Iqbal et al, 2018), cannabinoid production , and fiber retting process (Di Candilo et al, 2010;Ribeiro et al, 2015;Liu et al, 2017;Law et al, 2020). In this regard, exploring the microbiome of wild cannabis plants and ancestral heirloom cultivars within their native Eurasian habitats could be of crucial importance to identify beneficial microorganisms that have associated with cannabis over long evolutionary periods.…”
Section: Strategies To Identify Promising Pseudomonas Sppmentioning
confidence: 99%
“…Plant genotype, on the other hand, has a significant impact on associated microbiota ( Sapkota et al, 2015 ). Hemp microbiota manipulation has been suggested as a potential to help with fiber processing ( Law et al, 2020 ). Thus, significant consideration should be given to the microbiome of field-grown hemp, especially connecting yield and plant health.…”
Section: Introductionmentioning
confidence: 99%